Surface treatment process for multilayer ceramic substrates
By sequentially immersing the substrate in aqueous solutions of monobasic acid, dibasic acid, and tribasic acid, combined with a three-stage annealing process, the problem of incomplete impurity removal in the surface treatment of multilayer ceramic substrates was solved, thereby improving the integrity of the substrate structure and the yield rate.
Patent Information
- Application Number
- CN202610170109.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-06
- Publication Date
- 2026-05-26
- Estimated Expiration
- 2046-02-06
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic substrate technology, and more specifically, to a surface treatment process for multilayer ceramic substrates. Background Technology
[0002] The surface treatment process of multilayer ceramic substrates needs to go through three core stages: pretreatment, metallization and posttreatment. Among them, pretreatment is to remove the impurities and micro-defects remaining on the surface of the ceramic substrate, so as to provide a clean and uniform bonding interface for subsequent metallization.
[0003] Pickling is one of the key pretreatment steps in the surface treatment process of multilayer ceramic substrates. However, there are still some problems with pickling. Due to the large number of impurities on the surface of ceramic substrates, it is difficult to meet the removal requirements of different types of impurities. If the acid concentration is too high or the reactivity is too strong, it is easy to cause over-corrosion of the ceramic substrate surface, forming pits and grain boundary damage. If the concentration is too low or the reactivity is insufficient, it is impossible to completely remove the complex impurities remaining after co-firing, forming pickling blind zones.
[0004] If there are defects in the pickling process, the pits and residual impurities on the surface of the ceramic substrate will damage the contact interface between the metal layer and the ceramic substrate, causing the metal layer to fail to form a uniform and dense adhesion. The micro-cracks or grain boundary corrosion caused by pickling will weaken the structural strength of the ceramic substrate, making the substrate prone to breakage under subsequent cutting, assembly or vibration conditions, which will seriously affect the yield of the product and cause the production cost to rise sharply.
[0005] Therefore, it is necessary to propose a surface treatment process that can improve the yield of multilayer ceramic substrates. Summary of the Invention
[0006] This invention proposes a surface treatment process for multilayer ceramic substrates, which solves the problem of low yield of multilayer ceramic substrates in related technologies.
[0007] The technical solution of this invention is as follows: This invention proposes a surface treatment process for multilayer ceramic substrates, including the following steps:
[0008] S1. After drilling holes in the ceramic substrate, the pretreated ceramic substrate is obtained by grinding, pickling, annealing and post-treatment.
[0009] S2. The pretreated ceramic substrate is subjected to surface metallization treatment to obtain a metallized ceramic substrate.
[0010] S3. The metallized ceramic substrate is laminated, conductively cut and sintered to obtain a multilayer ceramic substrate; the pickling includes the following steps: the ground ceramic substrate is sequentially immersed in a monobasic acid aqueous solution, a dibasic acid aqueous solution and a tribasic acid aqueous solution, and then dried.
[0011] As a further technical solution, the concentration of the monocarboxylic acid aqueous solution is 5wt%~8wt%, for example, it can be 5wt%, 6wt%, 7wt%, 8wt%, preferably 6wt%; the soaking temperature of the monocarboxylic acid aqueous solution is 40~50℃, and the soaking time is 15~20min; the concentration of the dicarboxylic acid aqueous solution is 3wt%~5wt%, for example, it can be 3wt%, 4wt%, 5wt%, preferably 4wt%; the soaking temperature of the dicarboxylic acid aqueous solution is 50~60℃, and the soaking time is 20~25min; the concentration of the tricarboxylic acid aqueous solution is 2wt%~4wt%, for example, it can be 2wt%, 3wt%, 4wt%, preferably 3wt%; the soaking temperature of the tricarboxylic acid aqueous solution is 45~55℃, and the soaking time is 20~22min.
[0012] As a further technical solution, the monocarboxylic acid aqueous solution includes one of glacial acetic acid aqueous solution and formic acid aqueous solution, preferably glacial acetic acid aqueous solution.
[0013] As a further technical solution, the dicarboxylic acid aqueous solution includes one of oxalic acid aqueous solution, malonic acid aqueous solution, and adipic acid aqueous solution, preferably oxalic acid aqueous solution.
[0014] As a further technical solution, the tricarboxylic acid aqueous solution includes one of citric acid aqueous solution and phosphoric acid aqueous solution, preferably citric acid aqueous solution.
[0015] As a further technical solution, the multilayer ceramic substrate is one of alumina multilayer ceramic substrate, aluminum nitride multilayer ceramic substrate, and silicon nitride multilayer ceramic substrate, preferably an alumina multilayer ceramic substrate.
[0016] As a further technical solution, in step S1, the annealing includes the following steps: after the acid-washed ceramic substrate is dried, it is first heated to 300~350℃, preferably 300℃, and held at this temperature for 1~1.5h for the first stage of annealing, preferably 1h; then heated to 600~650℃, preferably 600℃, and held at this temperature for 2~2.5h for the second stage of annealing, preferably 2h; finally heated to 1050~1100℃, preferably 1100℃, and held at this temperature for 3~4h for the third stage of annealing, preferably 4h; and then cooled to room temperature.
[0017] As a further technical solution, the heating rate of the first stage of annealing is 5~8℃ / min, for example, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, preferably 6℃ / min; the heating rate of the second stage of annealing is 8~10℃ / min, for example, 8℃ / min, 9℃ / min, 10℃ / min, preferably 10℃ / min; and the heating rate of the third stage of annealing is 10~12℃ / min, for example, 10℃ / min, 11℃ / min, 12℃ / min, preferably 12℃ / min.
[0018] In the surface treatment process of the multilayer ceramic substrate of this invention, the low temperature of the first annealing stage combined with a low heating rate slowly releases the surface mechanical stress generated during polishing, avoiding surface cracking due to sudden stress release; the medium temperature of the second annealing stage combined with a moderate heating rate can alleviate the internal stress of the middle layer, while avoiding thermal stress caused by the temperature difference between the inside and outside due to excessive heating; the third annealing stage adopts a high temperature combined with a high heating rate to eliminate deep thermal stress and structural stress, realize the uniform and thorough release of internal stress in the entire thickness direction of the substrate, reduce the risk of fracture of the multilayer ceramic substrate due to stress, and improve the strength of the multilayer ceramic substrate.
[0019] As a further technical solution, in step S1, the grit of the sandpaper used for polishing is 600 to 800 grit, for example, it can be 600 grit, 700 grit, or 800 grit, preferably 800 grit.
[0020] As a further technical solution, the post-processing includes ultrasonic cleaning and baking, wherein the baking temperature is 120~130℃, preferably 120℃, and the baking time is 100~120min, preferably 120min.
[0021] As a further technical solution, the ultrasonic cleaning is water ultrasonic cleaning, the cleaning frequency is 20~40kHz, preferably 30kHz, and the conductivity of the water is 1~10us / cm, preferably 5us / cm.
[0022] The working principle and beneficial effects of this invention are as follows:
[0023] In the surface treatment process of the multilayer ceramic substrate of the present invention, the polished ceramic substrate is sequentially immersed in a monobasic acid aqueous solution, a dibasic acid aqueous solution, and a tribasic acid aqueous solution to improve the comprehensiveness and thoroughness of impurity removal and improve the yield of the multilayer ceramic substrate. In existing technologies, the pickling process of multilayer ceramic substrates is difficult to simultaneously remove different types of impurities and is prone to over-corrosion or pickling blind spots. In this invention, a pickling process using three acidic aqueous solutions is employed. Monobasic acid, with its strong reactivity, can quickly dissolve easily reactive metal oxide impurities on the substrate surface, clearing the basic obstacles for subsequent pickling. Dibasic acid, through its dicarboxyl group structure, can form stable complexes with insoluble salt impurities such as silicates and aluminates remaining on the substrate surface, achieving targeted removal of these stubborn impurities. Tribasic acid, relying on the synergistic effect of multiple functional groups, deeply removes deep impurities. The sequential immersion treatment with three acidic aqueous solutions can effectively avoid the problem of over-corrosion on the ceramic substrate surface, ensure the integrity of the substrate's microstructure, and effectively eliminate pickling blind spots caused by insufficient acid penetration in traditional pickling. This creates a clean interface foundation for subsequent metallization processing and improves the yield of multilayer ceramic substrates. Detailed Implementation
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] In the following examples and comparative examples:
[0026] The ceramic substrate is an alumina ceramic substrate.
[0027] Example 1
[0028] The surface treatment process for multilayer ceramic substrates includes the following steps:
[0029] S1. After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 20 minutes (concentration of glacial acetic acid aqueous solution is 6wt%, temperature is 40℃), then soaked in oxalic acid aqueous solution for 25 minutes (concentration of oxalic acid aqueous solution is 4wt%, temperature is 50℃), and finally soaked in citric acid aqueous solution for 22 minutes (concentration of citric acid aqueous solution is 3wt%, temperature is 45℃). After drying, the temperature is increased to 1100℃ at a heating rate of 6℃ / min and held for 7 hours. Then, it is ultrasonically cleaned with water with a conductivity of 5µs / cm at a frequency of 30kHz. After baking at 120℃ for 120 minutes, the pretreated ceramic substrate is obtained.
[0030] S2. After surface metallization treatment, the pre-treated ceramic substrate is obtained as a metallized ceramic substrate.
[0031] S3. After lamination (30 layers), conductive cutting and sintering, a multilayer ceramic substrate is obtained by metallizing the ceramic substrate.
[0032] Example 2
[0033] The surface treatment process for multilayer ceramic substrates includes the following steps:
[0034] S1. After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (concentration of glacial acetic acid aqueous solution is 6wt%, temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (concentration of oxalic acid aqueous solution is 4wt%, temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (concentration of citric acid aqueous solution is 3wt%, temperature is 50℃). After drying, the temperature is increased to 1100℃ at a heating rate of 6℃ / min and held for 7 hours. It is then ultrasonically cleaned with water with a conductivity of 5µs / cm at a frequency of 30kHz. After baking at 120℃ for 120 minutes, the pretreated ceramic substrate is obtained.
[0035] S2. After surface metallization treatment, the pre-treated ceramic substrate is obtained as a metallized ceramic substrate.
[0036] S3. After lamination (30 layers), conductive cutting and sintering, a multilayer ceramic substrate is obtained by metallizing the ceramic substrate.
[0037] Example 3
[0038] The surface treatment process for multilayer ceramic substrates includes the following steps:
[0039] S1. After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 15 minutes (concentration of glacial acetic acid aqueous solution is 6wt%, temperature is 50℃), then soaked in oxalic acid aqueous solution for 20 minutes (concentration of oxalic acid aqueous solution is 4wt%, temperature is 60℃), and finally soaked in citric acid aqueous solution for 20 minutes (concentration of citric acid aqueous solution is 3wt%, temperature is 55℃). After drying, the temperature is increased to 1100℃ at a heating rate of 6℃ / min and held for 7 hours. It is then ultrasonically cleaned with water with a conductivity of 5µs / cm at a frequency of 30kHz. After baking at 120℃ for 120 minutes, the pretreated ceramic substrate is obtained.
[0040] S2. After surface metallization treatment, the pre-treated ceramic substrate is obtained as a metallized ceramic substrate.
[0041] S3. After lamination (30 layers), conductive cutting and sintering, a multilayer ceramic substrate is obtained by metallizing the ceramic substrate.
[0042] Example 4
[0043] Compared with Example 2, Example 4 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃), and finally soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃). After drying, the temperature is raised to 1100℃ at a heating rate of 6℃ / min and kept at that temperature for 7 hours. Ultrasonic cleaning is performed using water with a conductivity of 5µs / cm at a frequency of 30kHz. After baking at 120℃ for 120 minutes, a pretreated ceramic substrate is obtained.
[0044] Example 5
[0045] Compared with Example 2, Example 5 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), then soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃), and finally soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃). After drying, the temperature is raised to 1100℃ at a heating rate of 6℃ / min and kept at that temperature for 7 hours. Ultrasonic cleaning is performed using water with a conductivity of 5µs / cm at a frequency of 30kHz. After baking at 120℃ for 120 minutes, a pretreated ceramic substrate is obtained.
[0046] Example 6
[0047] Compared with Example 2, Example 6 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), then soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, the temperature is raised to 1100℃ at a heating rate of 6℃ / min and kept at that temperature for 7 hours. Ultrasonic cleaning is performed using water with a conductivity of 5µs / cm at a frequency of 30kHz. After baking at 120℃ for 120 minutes, a pretreated ceramic substrate is obtained.
[0048] Example 7
[0049] Compared with Example 2, Example 7 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in a citric acid aqueous solution for 20 minutes (the concentration of the citric acid aqueous solution is 3wt%, and the temperature is 50℃), then soaked in a glacial acetic acid aqueous solution for 18 minutes (the concentration of the glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃); finally soaked in an oxalic acid aqueous solution for 22 minutes (the concentration of the oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), dried, heated to 1100℃ at a heating rate of 6℃ / min, held at that temperature for 7 hours, ultrasonically cleaned with water with a conductivity of 5µs / cm at a frequency of 30kHz, and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0050] Example 8
[0051] Compared with Example 2, Example 8 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃). After drying, the temperature is raised to 1100℃ at a heating rate of 6℃ / min and kept at that temperature for 7 hours. Ultrasonic cleaning is performed using water with a conductivity of 5µs / cm at a frequency of 30kHz. After baking at 120℃ for 120 minutes, a pretreated ceramic substrate is obtained.
[0052] Example 9
[0053] Compared with Example 2, Example 9 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 6℃ / min and held for 1 hour, then heated to 1100℃ at a heating rate of 10℃ / min and held for 6 hours. It is then ultrasonically cleaned with water with a conductivity of 5µs / cm at a frequency of 30kHz, and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0054] Example 10
[0055] Compared with Example 2, Example 10 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 6℃ / min and held for 1 hour, then heated to 1100℃ at a heating rate of 12℃ / min and held for 6 hours. It is then ultrasonically cleaned with water with a conductivity of 5µs / cm at a frequency of 30kHz, and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0056] Example 11
[0057] Compared with Example 2, Example 11 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 10℃ / min and held for 2 hours, then heated to 1100℃ at a heating rate of 12℃ / min and held for 5 hours. It is then ultrasonically cleaned with water with a conductivity of 5µs / cm at a frequency of 30kHz, and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0058] Example 12
[0059] Compared with Example 2, Example 12 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 6℃ / min and held for 1 hour, then heated to 600℃ at a heating rate of 10℃ / min and held for 2 hours, and finally heated to 1100℃ at a heating rate of 12℃ / min and held for 4 hours. It is then ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0060] Example 13
[0061] Compared with Example 2, Example 13 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 6℃ / min and held for 1 hour, then heated to 600℃ at a heating rate of 12℃ / min and held for 4 hours, and finally heated to 1100℃ at a heating rate of 10℃ / min and held for 2 hours. It is then ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0062] Example 14
[0063] Compared with Example 2, Example 14 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 10℃ / min and held for 2 hours, then heated to 600℃ at a heating rate of 6℃ / min and held for 1 hour, and finally heated to 1100℃ at a heating rate of 12℃ / min and held for 4 hours. It is then ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0064] Example 15
[0065] Compared with Example 2, Example 15 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 10℃ / min and held for 2 hours, then heated to 600℃ at a heating rate of 12℃ / min and held for 4 hours, and finally heated to 1100℃ at a heating rate of 6℃ / min and held for 1 hour. It is then ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0066] Example 16
[0067] Compared with Example 2, Example 16 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 12℃ / min and held for 4 hours, then heated to 600℃ at a heating rate of 10℃ / min and held for 2 hours, and finally heated to 1100℃ at a heating rate of 6℃ / min and held for 1 hour. It is then ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0068] Example 17
[0069] Compared with Example 2, Example 17 differs in that step S1 is different. In this example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 18 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), then soaked in oxalic acid aqueous solution for 22 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55℃), and finally soaked in citric acid aqueous solution for 20 minutes (the concentration of citric acid aqueous solution is 3wt%, and the temperature is 50℃). After drying, it is first heated to 300℃ at a heating rate of 12℃ / min and held for 4 hours, then heated to 600℃ at a heating rate of 6℃ / min and held for 1 hour, and finally heated to 1100℃ at a heating rate of 10℃ / min and held for 2 hours. It is then ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz and baked at 120℃ for 120 minutes to obtain the pretreated ceramic substrate.
[0070] Comparative Example 1
[0071] Compared with Example 2, Comparative Example 1 differs in that step S1 is different. In this comparative example, step S1 includes the following steps: after drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, immersed in glacial acetic acid aqueous solution for 60 min (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45℃), dried, heated to 1100℃ at a heating rate of 6℃ / min, kept at the temperature for 7 h, ultrasonically cleaned with water with a conductivity of 5 μs / cm at a frequency of 30 kHz, and baked at 120℃ for 120 min to obtain the pretreated ceramic substrate.
[0072] Comparative Example 2
[0073] Compared with Example 2, Comparative Example 2 differs in that step S1 is different. In this comparative example, step S1 includes the following steps: after drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, soaked in a citric acid aqueous solution for 60 minutes (the concentration of the citric acid aqueous solution is 3wt%, and the temperature is 50°C), dried, heated to 1100°C at a heating rate of 6°C / min, kept at the temperature for 7 hours, ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz, and baked at 120°C for 120 minutes to obtain the pretreated ceramic substrate.
[0074] Comparative Example 3
[0075] Compared with Example 2, Comparative Example 3 differs in that step S1 is different. In this comparative example, step S1 includes the following steps: After drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, first soaked in glacial acetic acid aqueous solution for 28 minutes (the concentration of glacial acetic acid aqueous solution is 6wt%, and the temperature is 45°C), then soaked in oxalic acid aqueous solution for 32 minutes (the concentration of oxalic acid aqueous solution is 4wt%, and the temperature is 55°C), dried, heated to 1100°C at a heating rate of 6°C / min, kept at the temperature for 7 hours, ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz, and baked at 120°C for 120 minutes to obtain the pretreated ceramic substrate.
[0076] Comparative Example 4
[0077] Compared with Example 2, Comparative Example 4 differs in that step S1 is different. In this comparative example, step S1 includes the following steps: after drilling holes in the ceramic substrate, it is polished with 800-grit sandpaper, immersed in sulfuric acid aqueous solution for 60 minutes (the concentration of sulfuric acid aqueous solution is 2wt%, and the temperature is 50°C), dried, heated to 1100°C at a heating rate of 6°C / min, kept at the temperature for 7 hours, ultrasonically cleaned with water with a conductivity of 5 μS / cm at a frequency of 30 kHz, and baked at 120°C for 120 minutes to obtain the pretreated ceramic substrate.
[0078] Experimental Example 1
[0079] For the multilayer ceramic substrates prepared in Examples 1-8 and Comparative Examples 1-4, their surface quality, mechanical properties, and insulation properties were evaluated. The surfaces were free of residual salts from acid washing, grinding dust, organic contaminants, etc., and showed no spots or color difference under white light after wiping, indicating they were qualified products. The bending strength of the samples was tested according to the test method (three-point bending method) specified in GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics". A bending strength > 300 MPa indicates a qualified product. The volume resistivity of the ceramic substrate was tested to be ≥ 10 Nm³ / s. 4 Ω·cm (tested at 25℃ and 500V DC voltage) indicates a qualified product; yield rate = (number of qualified substrates / total number of substrates tested) × 100%.
[0080] The test results are shown in Table 1:
[0081] Table 1 Performance test results of the multilayer ceramic substrates prepared in Examples 1-8 and Comparative Examples 1-4
[0082]
[0083] As shown in Table 1, immersing the ceramic substrate in monobasic acid aqueous solution, dibasic acid aqueous solution and tribasic acid aqueous solution in sequence helps to improve the yield of multilayer ceramic substrates.
[0084] Experiment Example 2
[0085] For the multilayer ceramic substrates prepared in Examples 2 and 9-17, the bending strength of the specimens was tested according to the test method (three-point bending method) specified in GB / T 6569-2006 "Test Method for Bending Strength of Fine Ceramics".
[0086] The test results are shown in Table 2:
[0087] Table 2 Performance test results of the multilayer ceramic substrates prepared in Examples 2 and 9-17
[0088]
[0089] As shown in Table 2, when a three-stage annealing process is used, and the heating rate of the first stage annealing is 5~8℃ / min, the heating rate of the second stage annealing is 8~10℃ / min, and the heating rate of the third stage annealing is 10~12℃ / min, the strength of the multilayer ceramic substrate can be improved.
[0090] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A surface treatment process for multilayer ceramic substrates, characterized in that, Includes the following steps: S1. After drilling holes in the ceramic substrate, the pretreated ceramic substrate is obtained by grinding, pickling, annealing and post-treatment. S2. The pretreated ceramic substrate is subjected to surface metallization treatment to obtain a metallized ceramic substrate. S3. The metallized ceramic substrate is laminated, conductively cut and sintered to obtain a multilayer ceramic substrate; the pickling includes the following steps: the polished ceramic substrate is sequentially immersed in a monobasic acid aqueous solution, a dibasic acid aqueous solution and a tribasic acid aqueous solution, and then dried; In step S1, the annealing includes the following steps: After acid pickling, the ceramic substrate is first heated to 300~350℃ and held for 1~1.5h for the first stage of annealing, then heated to 600~650℃ and held for 2~2.5h for the second stage of annealing, and finally heated to 1050~1100℃ and held for 3~4h for the third stage of annealing, and then cooled to room temperature. The heating rate of the first annealing stage is 5~8℃ / min, the heating rate of the second annealing stage is 8~10℃ / min, and the heating rate of the third annealing stage is 10~12℃ / min. The monocarboxylic acid aqueous solution includes one of glacial acetic acid aqueous solution and formic acid aqueous solution, with a concentration of 5wt%~8wt%; the dicarboxylic acid aqueous solution includes one of oxalic acid aqueous solution, malonic acid aqueous solution, and adipic acid aqueous solution, with a concentration of 3wt%~5wt%; the tricarboxylic acid aqueous solution includes one of citric acid aqueous solution and phosphoric acid aqueous solution, with a concentration of 2wt%~4wt%. The multilayer ceramic substrate is an alumina multilayer ceramic substrate.
2. The surface treatment process for multilayer ceramic substrates according to claim 1, characterized in that, The soaking temperature of the monocarboxylic acid aqueous solution is 40~50℃ and the soaking time is 15~20min; the soaking temperature of the dicarboxylic acid aqueous solution is 50~60℃ and the soaking time is 20~25min; and the soaking temperature of the tricarboxylic acid aqueous solution is 45~55℃ and the soaking time is 20~22min.
3. The surface treatment process for multilayer ceramic substrates according to claim 1, characterized in that, In step S1, the sandpaper used for polishing has a mesh size of 600 to 800.
4. The surface treatment process for multilayer ceramic substrates according to claim 1, characterized in that, The post-processing includes ultrasonic cleaning and baking, wherein the baking temperature is 120~130℃ and the baking time is 100~120min.
Citation Information
Patent Citations
Ceramic nozzle cleaning method based on semiconductor packaging
CN113210341A
Ceramic substrate circuit stack structure and preparation method thereof
CN117979544A
Surface treatment process of through hole thin film ceramic substrate
CN118248562A
